Virtual Summer Institutes as a Method of Rural Science Teacher Development - Thompson, Stephen L; Curcio, Rachelle; Adgerson, Amber; Harbour, Kristin E; D’Amico, Leigh Kale; West, Hall S; Roy, George J; Baker, Melissa A; Guest, Jessie; Compton-Lilly, Catherine (Theory & Practice in Rural Education, 2022)
Key Policy documents call for science teacher preparation programs to provide teacher candidates with approximations to authentic teaching experiences that occur in realistic contexts. Providing such opportunities for teacher candidates located in communities that are rural and geographically far from university settings is especially difficult. Stakeholders also point to the importance of positive coaching and mentoring relationships as key factors impacting the growth of teacher candidates. In this paper we discuss the positive potential of virtual science-related summer institutes as a vehicle to (a) provide authentic science teaching experiences for teacher candidates, and (b) promote the development of positive coaching and mentoring relationships. We also share features of a summer science institute developed as a launch to our teacher residency preparation program that incorporated teacher candidates, school-based teacher educators, and university-based supervisors to maximize the potential positive impacts. Data included quantitative and qualitative post-institute survey data from teacher candidates, school-based teacher educators, and university-based supervisors. Findings revealed that residents’ perception of their content knowledge development, pedagogical knowledge development, and overall effectiveness of the summer institute were high; additionally, school-based teacher educators and university-based supervisors indicated positive perceptions of the institute, noting their knowledge of coaching increased, helpful resources were provided, and institute structures promoted the development of positive coaching relationships. These results provide tentative evidence to support the continued use of virtual science summer institutes as a viable option for supporting both preservice and in-service teacher development.